2006
DOI: 10.1111/j.1439-0310.2006.01154.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Difference in Body Weight, Antler Length, Age or Dominance Rank related to the Number of Fights between Fallow Deer (Dama dama)?

Abstract: Competitive interactions between mature male fallow deer were investigated to determine whether antler length, body weight, age or dominance rank were related to the number of fights between individuals. Four different hypotheses were tested; the first predicted that body weight and antler length indicate individual quality and, therefore, as the difference between competitors in body weight and antler length increases, there should be a corresponding decrease in fight rate. The second and third hypotheses pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 81 publications
0
28
1
Order By: Relevance
“…Ninov (2003) also noted that the body weight of bucks dwelling in Bulgaria reached the highest point just before the rutting season, after which it rapidly decreased (even by 22.8%), and then slowly recovered to the normal level. Certainly, the body weight of males before mating may determine their social status in the herd (Jennings et al 2006). This fact was confirmed by McElligott et al (2001), who demonstrated that both the body size and measurements of males before the rutting season play the key role in shaping relationships among them.…”
Section: Discussionmentioning
confidence: 78%
“…Ninov (2003) also noted that the body weight of bucks dwelling in Bulgaria reached the highest point just before the rutting season, after which it rapidly decreased (even by 22.8%), and then slowly recovered to the normal level. Certainly, the body weight of males before mating may determine their social status in the herd (Jennings et al 2006). This fact was confirmed by McElligott et al (2001), who demonstrated that both the body size and measurements of males before the rutting season play the key role in shaping relationships among them.…”
Section: Discussionmentioning
confidence: 78%
“…When empiricists base their research firmly on a theoretical framework, most commonly either (1) predictions are derived from a general model and tested with a data set from a natural population providing the required information (Jennings et al. 2006; Porkert & Spinka 2006; Sergio et al.…”
mentioning
confidence: 99%
“…Empirical research in this field is based on formal evolutionary concepts, for instance on optimal foraging theory (Beauchamp 2006, 2007; Sanderson et al. 2006; Willisch & Ingold 2007) life history and contest theory (Jennings et al. 2006; Kemp et al.…”
mentioning
confidence: 99%
See 2 more Smart Citations